2004
DOI: 10.1080/09540120412331292525
|View full text |Cite
|
Sign up to set email alerts
|

Substance use and high-risk sex among men who have sex with men: a national online study in the USA

Abstract: This paper describes drug and sexual risk behaviors during a six-month period in 2001 of 2,916 gay and bisexual men who were recruited online. Bivariate and multivariate analyses examined correlates of unprotected anal intercourse (UAI). Drug and alcohol use were also examined by US region. UAI was associated with using alcohol or drugs, including poppers, crystal methamphetamine, cocaine, marijuana and Viagra before or during sex. Meeting sex partners both online and offline and having multiple sex partners w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
169
4
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(181 citation statements)
references
References 39 publications
6
169
4
2
Order By: Relevance
“…These findings also support results of previous studies (Balán, et al, 2009;Berg & Grimes, 2010;Elford, Bolding, & Sherr, 2001;Mettey, Crosby, DiClemente, & Holtgrave, 2003;Poon, et al, 2013), that inform the use of internet to meet online sex partners for offline sex and transactional sex as the common practices that contributed to unprotected sexual behaviours among MSM populations. On the contrary, other practices including the use of drugs and excessive alcohol consumption, which have been widely reported as associated with UAI among MSM (Clutterbuck, Gorman, McMillan, Lewis, & Macintyre, 2001;Drumright et al, 2006;Hirshfield, Remien, Humberstone, Walavalkar, &Chiasson, 2004;Parsons &Halkitis, 2002), were not found to be the case in the current study.…”
Section: Discussioncontrasting
confidence: 48%
“…These findings also support results of previous studies (Balán, et al, 2009;Berg & Grimes, 2010;Elford, Bolding, & Sherr, 2001;Mettey, Crosby, DiClemente, & Holtgrave, 2003;Poon, et al, 2013), that inform the use of internet to meet online sex partners for offline sex and transactional sex as the common practices that contributed to unprotected sexual behaviours among MSM populations. On the contrary, other practices including the use of drugs and excessive alcohol consumption, which have been widely reported as associated with UAI among MSM (Clutterbuck, Gorman, McMillan, Lewis, & Macintyre, 2001;Drumright et al, 2006;Hirshfield, Remien, Humberstone, Walavalkar, &Chiasson, 2004;Parsons &Halkitis, 2002), were not found to be the case in the current study.…”
Section: Discussioncontrasting
confidence: 48%
“…As others have noted, the use of substances has serious implications for the use of safer sex techniques (Hirshfield et al, 2004). The use of substances alone can impair judgment and seriously affect the ability to make sexual health decisions among homeless youth.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have found increased illicit drug use among Internet-using men, specifically poppers (nitrite inhalants), MDMA (ecstasy), crystal methamphetamine, and Viagra\, 3,27,28 others have found no differences in the use of these drugs. 8 With regard to demographic characteristics, it has been reported that men using the Internet for sex are more likely to be white 3,4,20,[28][29][30] and have less education; 19 however, other studies have found no differences in race/ethnicity 8,17 or level of education. 3,17 Demographic characteristics have been shown to be dependent on the website men are recruited from; for example, men recruited from America Online tended to be older than those recruited from Gay.com.…”
Section: Demographic and Behavioral Characteristics Of Msm Onlinementioning
confidence: 93%
“…8 An online study in the US found that only 12% of HIV-positive men with more than one sex partner in the 6 months before the survey reported serosorting. 30 HIV-negative men with online partners are more likely to report having HIV-positive partners, 17 more likely to report unsafe anal sex with nonconcordant partners, 18 more likely to report receiving money or drugs for sex, 17 and report feeling less worry about HIV due to improved HIV treatments. 18 These findings are concerning because of the increased potential for HIV infection among HIV-negative men who use the Internet to find sex partners.…”
Section: Hiv and Sti Transmissionmentioning
confidence: 99%